2015
DOI: 10.1097/mib.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Combined Immunosuppression Impairs Immunogenicity to Tetanus and Pertussis Vaccination Among Patients with Inflammatory Bowel Disease

Abstract: Antibody responses to tetanus and pertussis vaccination may be affected by therapeutic drug regimen. Patients with IBD should optimally receive Tdap before starting immunomodulators, particularly when used in combination with anti-tumor necrosis factor alpha agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…A prospective controlled study from 2015 investigated serological immune responses to tetanus and pertussis booster vaccination in 84 IBD patients. This study found a reduced response rate among immunosuppressed patients, the lowest among those on a combined biologic and immunomodulator therapy [33]. Tetanus, diphtheria, and pertussis vaccination should be given according to general country-specific vaccination guidelines.…”
Section: Inactivated Vaccinations Influenzamentioning
confidence: 75%
“…A prospective controlled study from 2015 investigated serological immune responses to tetanus and pertussis booster vaccination in 84 IBD patients. This study found a reduced response rate among immunosuppressed patients, the lowest among those on a combined biologic and immunomodulator therapy [33]. Tetanus, diphtheria, and pertussis vaccination should be given according to general country-specific vaccination guidelines.…”
Section: Inactivated Vaccinations Influenzamentioning
confidence: 75%
“…An increased prevalence of rheumatoid arthritis has been reported in UC patients. Previous studies have also demonstrated that the pertussis vaccine was immunogenic and safe in pediatric patients with UC, particularly when used in combination with anti-TNF- α agents [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBD generally mount appropriate responses to vaccinations, although patients ≥65 years old and patients on biologics and/or immune-modifying agents may have a decreased immune response to vaccinations [16-21]. Therefore, particularly in the elderly, obtaining antibody titers and appropriate vaccinations before the initiation of immunosuppressive therapy may be especially important.…”
Section: Vaccinationsmentioning
confidence: 99%
“…Although the immune system’s response to such vaccines may be diminished in older patients and in patients on immunosuppressive therapy [17-21], it is still important to administer the recommended vaccines, as the majority of these patients may still develop sufficient antibodies to provide protection [16,21,32]. …”
Section: Vaccinationsmentioning
confidence: 99%